Designing a Measurement Model for the Effectiveness of Online Learning Using C4.5 Algorithm - Siti Mukodimah; Handoyo Widi Nugroho; Muhamad Muslihudin (Proceeding International Conference on Information Technology and Business, 2021)
Technological developments in the world of education have led to many innovations to support education such as online learning in the learning process amid the Covid19 pandemic. Changes in learning methods that occur suddenly from conventional learning methods or directly switch to distance learning methods or using online learning media greatly impact and affect students who come from underprivileged families and students who are in areas where internet access and infrastructure are lacking. support. This study aims to create a classification model for measuring the effectiveness of online learning in the Pringsewu area using the classification method. The classification method is used to classify data based on the nature of the data that has been recognized by each class. Various methods can be used to classify data, namely the C4.5 Algorithm method. The results of the research carried out are a design classification model for measuring the effectiveness of online learning in the Pringsewu area such as Internet Access, Network Infrastructure, Learning Media, Device Networks, Mastery of Technology Operations, School ICT Infrastructure, Learning Concepts, Motivation in Online Learning, Understanding of Learning Materials.Keywords—Design, Effectiveness, Online Learning, C4.5 Algoritm